Transparent TiO2 and ZnO Thin Films on Glass for UV Protection of PV Modules - Johansson, Wilhelm; Peralta, Albert; Jonson, Bo; Anand, Srinivasan; Österlund, Lars; Karlsson, Stefan (Frontiers in Materials, 2019)
Failure of PV modules frequently occurs as a result of degradation of its encapsulation by destructive UV radiation. Both the life expectancy and efficiency of PV modules can be improved by reducing the transmittance of the destructive UV radiation through the cover glass without compromising the transmittance in the visible wavelength region. In addition, if the absorbed UV photons can be down-shifted to wavelengths that can be more efficiently converted to electrical energy, an additional increase of the PV efficiency could be achieved. In this study we have investigated transparent ZnO and TiO2 thin films deposited by spray pyrolysis on soda lime silicate float glass as functional layers on PV cover glass. The optical bandgap, UV-cutoff, UV-Vis transmittance, reflectivity (total and diffuse) and photoluminescence have been determined. The ZnO coating shifted the optical bandgap to longer wavelengths, resulting in a reduction of the transmittance of destructive UV radiation by up to approximately 85 %. Distinct photoluminescence peak at 377 nm and at 640 nm were observed for one of the ZnO samples. The TiO2 coated glasses also showed an increased UV cut-off, which resulted in a reduction of transmittance of destructive UV radiation by up to 75%. However, no photoluminescence peaks could be observed from the TiO2 films with 325 nm excitation laser and can be explained by the fact that only indirect interband transitions are accessible at this excitation wavelength. Deposition of both ZnO and TiO2 coatings resulted in a reduction of the transmitted light convertible by PV modules, by up to 12.3 and 21.8%, respectively. The implication of the results is discussed in terms of lifetime expectancy and efficiency of PV modules.